2007
DOI: 10.1111/j.1365-2796.2007.01862.x
|View full text |Cite
|
Sign up to set email alerts
|

C‐reactive protein, interleukin‐6, secretory phospholipase A2 group IIA and intercellular adhesion molecule‐1 in the prediction of late outcome events after acute coronary syndromes

Abstract: . Objective.  We investigated whether levels of C‐reactive protein (CRP), interleukin‐6 (IL‐6), secretory phospholipase A2 group IIA (sPLA2‐IIA) and intercellular adhesion molecule‐1 (ICAM‐I) predict late outcomes in patients with acute coronary syndromes (ACS). Design.  Prospective longitudinal study. CRP (mg L−1), IL‐6 (pg mL−1), sPLA2‐IIA (ng mL−1) and ICAM‐1 (ng mL−1) were measured at days 1 (n = 757) and 4 (n = 533) after hospital admission for ACS. Their relations to mortality and rehospitalization for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
36
1
1

Year Published

2009
2009
2019
2019

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 52 publications
(41 citation statements)
references
References 43 publications
(58 reference statements)
3
36
1
1
Order By: Relevance
“…Similar findings have been reported in patients with congestive heart failure [28] and in patients with acute coronary syndromes [29]. IL-6 is produced not only by leukocytes [30], but also by the vascular tissue, both endothelial and SMCs, and myocytes and fibroblasts in various organs, including the lung.…”
Section: Discussionsupporting
confidence: 71%
“…Similar findings have been reported in patients with congestive heart failure [28] and in patients with acute coronary syndromes [29]. IL-6 is produced not only by leukocytes [30], but also by the vascular tissue, both endothelial and SMCs, and myocytes and fibroblasts in various organs, including the lung.…”
Section: Discussionsupporting
confidence: 71%
“…Similarly, we recently reported that there is a direct relationship between an increase in the levels of apoC-III, serum TG, acute inflammatory process markers such as IL-6, and a decrease of HDL-C in the oliguric phase of hemorrhagic fever renal syndrome (HFRS) patients (Cho et al, 2008). In addition, Hartford et al (2007) reported that CRP, IL-6, and sPLA2 are intercorrelated in patients with ACS, whereas iCAM-1 appears to respond differently to acute coronary events. Recently Suzuki et al (2008) reported that elevation of matrix metalloproteinases and IL-6 are involved in the instability of vulnerable plaque associated with the induction of myocardial infarction.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, although several biomarkers have been reported to predict cardiovascular risk, there have been no useful biomarkers developed for the early detection of MI (Pahor et al, 1999). Inflammation is a major risk factor of atherosclerosis, and several inflammatory biomarkers such as high sensitivity C-reactive protein (hsCRP), cytokines, biomarkers of endothelial cell activation, and proinflammatory enzymes have been established for the diagnosis of ACS (Hartford et al, 2007); however, no studies have been reported to determine if these biomarkers are useful for the prediction of acute MI.…”
Section: Introductionmentioning
confidence: 99%
“…Attempts to predict readmission after AMI have relied [24][25][26][27][28] are known to predict readmission after a coronary event, none is measured routinely in clinical practice at present and we do not know which biomarker or combination will yield the best prediction. There are several known clinical and demographic risk factors for readmission after AMI, [5][6][7][8]29 but their individual predictive power is relatively low and models derived from such factors have performed poorly.…”
Section: Discussionmentioning
confidence: 99%